PROBLEM OF IODINE SCARCE DISEASES IN UKRAINE AND WAYS OF OVERCOMING - Йонда, М Є.; Суслик, З. Б.; Мищенко, І. А.; Гречух, Л. С.; Погорілий, М. П.; Малишевська, О. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In deciding the problem of iodine deficiency in Ukraine and methods of combating it is important to develop effective means for prevention and treatment of iodine deficiency disorders. The paper analyzed the literature data on the problem of iodine deficiency and ways and means to overcome it.